Tax Haven Incorporation and the Cost of Capital* - Lewellen, Christina M.; Mauler, Landon; Watson, Luke (Contemporary Accounting Research, 2021)
ABSTRACT Incorporating the firm's corporate parent in a tax haven is a major decision that receives significant attention from many stakeholders, yet certain implications of this corporate strategy remain unclear. While tax haven incorporation offers tax savings, it also imposes risks that are potentially costly and hence important to consider. We predict and find a higher cost of equity capital in firms with parent companies that are incorporated in tax havens but that are primarily based in nonhaven countries. We also predict and find that the observed cost of equity premium is more pronounced in firms with greater tax risk, firm‐level information risk, and country‐level legal risk. We also employ corporate inversions in a difference‐in‐differences test and again find a positive relation between tax haven parent incorporation and the cost of capital. Our findings imply that an increased cost of capital is a material cost of tax haven parent incorporation. We contribute to the literatures on valuation of tax haven use, tax and nontax costs of corporate tax strategies, corporate inversions, and the relation between taxes and the cost of capital. Our study provides evidence on the tax and nontax risks of a uniquely observable tax strategy (i.e., tax haven parent incorporation) that could factor into firms' decisions about whether to incorporate in a tax haven and policymakers' efforts to deter such activity.